2021
DOI: 10.1177/0963721420978609
|View full text |Cite
|
Sign up to set email alerts
|

Robots as Mirrors of the Human Mind

Abstract: Robots are currently the center of attention in various fields of research because of their potential use as assistants for daily living. In this article, I highlight a different role that robots can play—being a tool for understanding human cognition. I provide examples in which robots have been used in experimental psychology to study sociocognitive mechanisms such as joint attention and sense of agency. I also discuss the issue of whether and when robots (especially those that resemble humans) are perceived… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…This line of research is part of the project: “Intentional Stance for Social attunement (INSTANCE, https://www.instanceproject.eu/),” funded by the European Research Council. The project investigates mechanisms of social cognition by means of using humanoid robots as sophisticated “stimuli” providing more ecological validity than 2D stimuli presented on a screen (for a similar line of argumentation, see Wiese et al, 2017; Wykowska, 2021). The experiments presented here extend our previous studies by addressing a new question of interest, namely what is the relationship between modulatory activity of social signals (i.e., eye contact) and strategic cognitive control in gaze cuing.…”
Section: Discussionmentioning
confidence: 99%
“…This line of research is part of the project: “Intentional Stance for Social attunement (INSTANCE, https://www.instanceproject.eu/),” funded by the European Research Council. The project investigates mechanisms of social cognition by means of using humanoid robots as sophisticated “stimuli” providing more ecological validity than 2D stimuli presented on a screen (for a similar line of argumentation, see Wiese et al, 2017; Wykowska, 2021). The experiments presented here extend our previous studies by addressing a new question of interest, namely what is the relationship between modulatory activity of social signals (i.e., eye contact) and strategic cognitive control in gaze cuing.…”
Section: Discussionmentioning
confidence: 99%
“…This approach pushes further than the focus on individual regions or few domain-specific networks involved in social cognitive processes often used in the literature Wiese et al, 2017;Wykowska, 2021). Using this network approach, we replicate and extend the original study by Rauchbauer and colleagues (2019).…”
Section: Discussionmentioning
confidence: 64%
“…Together activity in these networks influence the quality and outcome of an interaction (Feng et al, 2021;Redcay & Schilbach, 2019), for example level of affiliation and degree of trust. In recent years, studies have begun to ask if these networks extent to other social agents and support engagement with robots Wykowska, 2021). While most studies so far have been focussing on activity during the perception of robots in a small number of regions mostly within the social domain, a careful assessment of the functional architecture during real interactions with robots is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as Hofstede posited a dimension named "indulgence", which addressed the extent to which a society values leisure time, moral discipline, happiness, and well-being (Enkh-Amgalan, 2016). Khans and Cox reported that indulgent cultures tend 2 We administered and analyzed also the other subscales to control for covariance. This is a provisional file, not the final typeset article to create new technology as a way to improve life, to value the expression of emotions and freedom of speech.…”
Section: Task Procedures and Measuresmentioning
confidence: 99%
“…As humans become exposed to robot presence, it is crucial to examine how robots are represented in the human mind, and how robot actions are perceived and interpreted. (for a review see Wykowska, 2021). Previous studies have shown that people differ in the degree of anthropomorphism [3], [4] and in the likelihood of attributing intentionality to robot actions (Marchesi et al, 2019;Bossi et al, 2020, Hegel et al, 2008Thellman & Ziemke, 2020).…”
Section: Introductionmentioning
confidence: 99%